Facts or Ideology: What Determines the Results of Econometric Estimates of the Deterrence Effect of Death Penalty? A Meta-Analysis - Berit C. Gerritzen; Gebhard Kirchgässner (Center for Economic Studies and ifo Institute (CESifo), 2013)
Provided that the literature on the deterrent effect of capital punishment is overall inconclusive, the fact that individual authors persistently claim to have found solid evidence in one or the other direction raises two questions. Firstly, what are the causes for these different results? Do different data samples, estimation methods or time periods lead to different results or do the outcomes merely reflect prior convictions of the authors? Secondly, to what extent is it possible to derive such diverging results by slightly changing the specification of the test equations without violating scientific standards? After a survey of the over forty reviews of this literature available so far, we perform a meta-analysis of 102 deterrence studies published between 1975 and 2011. The profession of the author turns out to be the only statistically significant explanatory variable: Economists claim significantly more often to have found a significant deterrence effect than members of law or other social science departments. Furthermore, using a panel data set of U.S. states, we show how easy it is to derive contradictory results by employing alternative specifications. Thus, our results reinforce the claim that the empirical evidence presented to date is by far too fragile in order to base political decisions on it.
Keywords: K14; K42; 330; death penalty; deterrence; econometric evidence; ideology